Similar Characteristics of siRNAs of Plant Viruses Which Replicate in Plant and Fungal Hosts - Tianxing Pang; Jianping Peng; Ruiling Bian; Yu Liu; Dong Zhang; Ida Bagus Andika; Liying Sun (Biology, 2022)
RNA silencing is a host innate antiviral mechanism which acts via the synthesis of viral-derived small interfering RNAs (vsiRNAs). We have previously reported the infection of phytopathogenic fungi by plant viruses such as cucumber mosaic virus (CMV) and tobacco mosaic virus (TMV). Furthermore, fungal RNA silencing was shown to suppress plant virus accumulation, but the characteristics of plant vsiRNAs associated with the antiviral response in this nonconventional host remain unknown. Using high-throughput sequencing, we characterized vsiRNA profiles in two plant RNA virus–fungal host pathosystems: CMV infection in phytopathogenic fungus Rhizoctonia solani and TMV infection in phytopathogenic fungus Fusarium graminearum. The relative abundances of CMV and TMV siRNAs in the respective fungal hosts were much lower than those in the respective experimental plant hosts, Nicotiana benthamiana and Nicotiana tabacum. However, CMV and TMV siRNAs in fungi had similar characteristics to those in plants, particularly in their size distributions, proportion of plus and minus senses, and nucleotide preference for the 5′ termini of vsiRNAs. The abundance of TMV siRNAs largely decreased in F. graminearum mutants with a deletion in either dicer-like 1 (dcl1) or dcl2 genes which encode key proteins for the production of siRNAs and antiviral responses. However, deletion of both dcl1 and dcl2 restored TMV siRNA accumulation in F. graminearum, indicating the production of dcl-independent siRNAs with no antiviral function in the absence of the dcl1 and dcl2 genes. Our results suggest that fungal RNA silencing recognizes and processes the invading plant RNA virus genome in a similar way as in plants.